Diasporas of the modern Middle East (Edinburgh)
vii, 416 s.
Keywords: "Approaching the Middle East through the lens of Diaspora Studies, the 11 detailed case studies in this volume explore the experiences of different diasporic communities in and of the region, and look at the changing conceptions and practice of diaspora in the modern Middle East. They show how concepts central to diaspora such as 'homeland', 'host state', 'exile', 'longing', 'memory' and 'return' have been deconstructed and reinstated with new meaning through each complex diasporic experience. They also examine how different groups have struggled to claim and negotiate a space for themselves in the Middle East, and the ways in which these efforts have been aided and hampered by the historical, social, legal, political, economic, colonial and post-colonial specificities of the region. In situating these different communities within their own narratives - of conflict, resistance, war, genocide, persecution, displacement, migration - these studies stress both the common elements of diaspora but also their individual specificity in a way that challenges, complements and at times subverts the dominant nationalist historiography of the region. Key Features:Includes 11 detailed qualitative case studies based on extensive fieldwork and research. Provides a counter history to prevailing nationalist narratives. Engages the new theoretical and conceptual developments of Diaspora Studies with the empirical richness and dynamism of Middle Eastern Studies. Case studies include Greek Orthodox communities in Syria and Turkey, the late Ottoman elites, the Ossetians in Turkey, the Italians of Egypt, the Cypriot Armenian community, Armenian diasporic tourism in Turkey, Palestinians in Lebanon, Malayalees in the Gulf, Iraqis in Egypt, and Lebanese diaspora literature" --